ANALISIS STRATEGI PT INDOSAT, TBK. UNTUK PENINGKATAN JUMLAH PELANGGAN PASCABAYAR MELALUI TELESALES - , Retno Wulan Kartiko Purbodjati, Ertambang Nahartyo, Phd. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was conducted to analyze the strategy of Indosat Telesales in order to improve the market share of postpaid customer in Indosat. Data and information used in this research are collected from interviews with Telesales Staff Division and other related divisions, Telesales reports and also from public data which were retrieved from financial report and from internet. The research methods used are external analysis using PEST (Politic, Economy, Social and Technology), Five Forces Analysis, and internal analysis by looking at some functions (human resources management, product, sales and revenue, operation) and SWOT analysis (Strengths, Weaknesses, Opportunities and Threats). The results of the research that can be concluded that the telesales strategy has strong and weak points and also provide alternative strategies that can be executed by Indosat Telesales to improve the postpaid sales volume.